2011
DOI: 10.3747/co.v18i5.775
|View full text |Cite
|
Sign up to set email alerts
|

Canadian College of Medical Geneticists Guidelines for the Indications, Analysis, and Reporting of Cancer Specimens

Abstract: The Canadian College of Medical Geneticists (ccmg) is a national organization of medical and laboratory geneticists. The mission of the ccmg is to establish and maintain high-quality professional and ethical standards for medical genetics services in Canada and to help to ensure that service of the highest quality is delivered to the Canadian public. Cancer cytogenetics is one of the sections of practice of the ccmg. The ccmg Cytogenetic Committee has, therefore, put forward guidelines to provide oncologists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Chromosomes X, 21, and 22 have been reported to be susceptible to whole chromosome errors [46][47][48]. Chromosomes 2, 6, 7, 11, 14, 15, 16, and 20 are known to be associated with UPD [49,50]. Recent findings showed that chromosome length had a positive correlation with the mitotic error of each chromosome, but a negative correlation with the meiotic error of the preimplantation embryo [47,51].…”
Section: Specific Chromosomes Involvedmentioning
confidence: 99%
“…Chromosomes X, 21, and 22 have been reported to be susceptible to whole chromosome errors [46][47][48]. Chromosomes 2, 6, 7, 11, 14, 15, 16, and 20 are known to be associated with UPD [49,50]. Recent findings showed that chromosome length had a positive correlation with the mitotic error of each chromosome, but a negative correlation with the meiotic error of the preimplantation embryo [47,51].…”
Section: Specific Chromosomes Involvedmentioning
confidence: 99%
“…Routine PCR based assays can be rapid, but a priori knowledge of the fusion breakpoints is required and when fusions involve large intronic regions RNA input are generally needed. Thus, turn-around times for these methods can take three days to two weeks [13, 14]. To capitalize on the potential of precision medicine, faster analysis of sequencing data is needed to improve the potential of molecular-assisted cancer diagnoses [15].…”
Section: Main Textmentioning
confidence: 99%
“…Routine PCR based assays can be rapid, but a priori knowledge of the fusion breakpoints is required and when fusions involve large intronic regions RNA input are generally needed. Thus, turn-around times for these methods can take three days to two weeks [13,14].…”
mentioning
confidence: 99%
“…Some of the other factors that impact the culture growth, include; hypocellularity, low proliferative rate in tissue culture, insufficient number of metaphases, less viability of cells, disease and the treatment induced cytotoxicity [ 7 ]. The failure rate for bone marrow and neoplastic blood specimen cultures should not exceed 10% [ 4 ]…”
Section: Introductionmentioning
confidence: 99%